Mechanical properties and biocompatibility of polymer infiltrated sodium aluminum silicate restorative composites - Huining Wang; Bencang Cui; Jing Li; Shu Li; Yuanhua Lin; Deping Liu; Ming Li (Journal of Advanced Ceramics, 2017)
Abstract A new type of polymer-infiltrated-ceramic-network composites (PICNs) was fabricated by infiltrating methacrylate-based monomers into partially sintered porous ceramics. The mechanical properties (flexural strength, flexural modulus, elastic modulus, Vickers hardness, fracture toughness) were investigated and compared with that of the natural tooth and common commercial CAD/CAM blocks. Our results indicated that sintering temperature and corresponding density of porous ceramics have an obvious influence on the mechanical properties, and PICNs could highly mimic the natural tooth in mechanical properties. The biocompatibility experiments evaluated through in vitro cell attachment and proliferation of BMSCs showed good biocompatibility. The mechanical properties and biocompatibility confirmed that PICN could be a promising candidate for CAD/CAM blocks for dental restoration.